Politik Luar Negeri Bebas Aktif dan Prinsip Universal Hak Asasi Manusia dalam Kaitannya terhadap Dukungan Negara Indonesia Kepada Kemerdekaan Negara Palestina - Agatha Eka Febriani Hangin; Amelia Pawestri; Aulia Azzahwa Salsabilla; Moch. Faruq; Nestoresi Jalung (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
Indonesia has long demonstrated its solidarity with the Palestinian people as a reflection of its free and active foreign policy and commitment to human rights. This study aims to examine how Indonesia’s stance toward the humanitarian crisis in Gaza embodies the principles of a free and active foreign policy and aligns with the human rights values enshrined in the 1945 Constitution and the Universal Declaration of Human Rights. Using a normative juridical approach, this research analyzes relevant laws, policies, and official government statements. The findings show that Indonesia’s support for Palestine is not a form of political alignment, but rather a moral expression of justice and humanity. Through active diplomacy, humanitarian assistance, and participation in international forums, Indonesia consistently promotes peace and the enforcement of international humanitarian law. Thus, Indonesia’s position reflects a balance between the principles of a free and active foreign policy and the universal protection of human rights.